Упростить выражения (1+n/n^2-nm-1-m/m^2-nm)*(m+n/m^2n-n^2m)^-1

0 голосов
116 просмотров

Упростить выражения (1+n/n^2-nm-1-m/m^2-nm)*(m+n/m^2n-n^2m)^-1


Алгебра (12 баллов) | 116 просмотров
Дан 1 ответ
0 голосов

Решите задачу:

\frac{1+n}{n^2-nm}-\frac{1-m}{m^2-nm}*(\frac{m+n}{m^2n-n^2m})^{-1}=\\ \frac{1+n}{n(n-m)}-\frac{1-m}{m(m-n)}*(\frac{m+n}{mn(m-n)})^{-1}=\\ \frac{1+n}{n(n-m)}+\frac{1-m}{m(n-m)}*\frac{mn(m-n)}{(m+n)}=\\ \frac{m+mn}{mn(n-m)}+\frac{n-nm}{mn(n-m)}*\frac{mn(m-n)}{(m+n)}=\\ \frac{(m+mn+n-nm)}{mn(n-m)}*\frac{mn(m-n)}{(m+n)}=\\ \frac{(m+n)}{mn(n-m)}*\frac{mn(m-n)}{(m+n)}=-1\\

(26.0k баллов)